Role of Mental Disorders in Nosocomial Infections after Hip Fracture Treatment - Guerado, Enrique; Cano, Juan Ramon; Cruz, Encarnacion; Benitez-Parejo, Nicolás; Perea-Milla, Emilio (Interdisciplinary Perspectives on Infectious Diseases, 2010)
The association between mental disorders (MDs) and iatrogenic complications after hip fracture surgery has been poorly studied. Among iatrogenic complications, nosocomial infections (NIs) are a major factor in hip fracture surgery. The aim of this paper was to determine whether patients with a MD and a hip fracture develop more NIs after hip surgery than patients with no MD. We studied 912 patients who underwent surgery for a hip fracture (223 patients with a MD who underwent surgery for a hip fracture and 689 control patients without a MD who also underwent surgery for a hip fracture) and followed them after surgery. Univariable and multivariable analyses were performed using simple and multiple logistic regression analysis (confidence interval, crude and adjusted odds ratios, and P value). We found that MDs, gender, and comorbidities were not associated with a higher risk of developing a NI after surgery for a hip fracture. Only age increases the risk of a NI.